2019
DOI: 10.1159/000501099
|View full text |Cite
|
Sign up to set email alerts
|

Digital Analysis in Breast Imaging

Abstract: Breast imaging is a multimodal approach that plays an essential role in the diagnosis of breast cancer. Mammography, sonography, magnetic resonance, and image-guided biopsy are imaging techniques used to search for malignant changes in the breast or precursors of malignant changes in, e.g., screening programs or follow-ups after breast cancer treatment. However, these methods still have some disadvantages such as interobserver variability and the mammography sensitivity in women with radiologically dense breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…The preliminary results provide scopes for the further exploration of CNN. In an analysis conducted by [ 39 ], it was reported that there is an urgent need to improve imaging analysis and explore detection techniques using AI for breast cancer detection. Breast cancer is determined by several abnormalities and thus, this work contributes in detecting and classifying these abnormalities.…”
Section: Results and Performance Evaluationmentioning
confidence: 99%
“…The preliminary results provide scopes for the further exploration of CNN. In an analysis conducted by [ 39 ], it was reported that there is an urgent need to improve imaging analysis and explore detection techniques using AI for breast cancer detection. Breast cancer is determined by several abnormalities and thus, this work contributes in detecting and classifying these abnormalities.…”
Section: Results and Performance Evaluationmentioning
confidence: 99%
“…Research has shown that the application of artificial intelligence and machine learning during diagnosis has helped further improve cancer detection and staging [11,12]. Computer-aided diagnosis has helped with automating labor-intensive steps and reducing reader bias [13][14][15]. Several studies have shown that accurate breast cancer predictions may depend on the right combination of feature selection and/or ML techniques [16,17].…”
Section: Introductionmentioning
confidence: 99%